2016
DOI: 10.5812/ircmj.29344
|View full text |Cite
|
Sign up to set email alerts
|

Respect to Women’s Autonomy in Childbirth: A Qualitative Study

Abstract: Background: Respect to women's autonomy in vaginal child birth is a key factor of maternity care. Engaging women in decisionmaking in vaginal delivery helps women have a positive experience of delivery. Objectives: In this content analysis of qualitative study we explored experiences of mothers and midwives in women's role in normal vaginal childbirth. Methods: This study was conducted in 2013 -2014 in Iran. Overall 23 women and midwives were evaluated in this study. Data collected from 12 women and 11 midwive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…It has also been reported that mobility during the first stage of labour is safe 38. Denying women autonomy, or not respecting women’s choices during childbirth without a justifiable medical reason, constitutes mistreatment that negatively affects their overall childbirth experience 42…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that mobility during the first stage of labour is safe 38. Denying women autonomy, or not respecting women’s choices during childbirth without a justifiable medical reason, constitutes mistreatment that negatively affects their overall childbirth experience 42…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, the social context appears to be a crucial determinant of the impact of empowerment on women's health and well-being throughout the childbirth process [13][14][15]. One study that focused on vaginal delivery demonstrated the difficulty of ensuring that women's autonomy is respected and the crucial role of women's empowerment in childbirth regarding access to information, the presentation of self-assertion and a woman's relationship with midwives [16]. One cause of high rates of CS that is linked to women's empowerment is women's request for CS, which reaches a high level in middle-income countries [17].…”
Section: Introductionmentioning
confidence: 99%